Energetic neutral atoms assisted development of kithul (Caryota urens) starch–lauric acid complexes: A characterisation study. (15th December 2020) - Sudheesh, Cherakkathodi; Sunooj, Kappat Valiyapeediyekkal; Bhavani, Balasubhramaniam; Aaliya, Basheer; Navaf, Muhammed; Akhila, Plachikkattu Parambil; Sabu, Sarasan; Sasidharan, Abhilash; Sinha, Suraj Kumar; Kumar, Sunny; Sajeevkumar, Vallayil Appukuttan; George, Johnsy
Abstract: Kithul starch was treated by EN (energetic neutral nitrogen) atoms at 6 W, 12 W and 18 W for 15 min and incorporated lauric acid for the development of starch-lauric acid inclusion complexes. EN atoms treatment significantly (p ≤ 0.05) increased the complex index (CI). Severe morphological alterations on the kithul starch granules by EN atoms treatment enhanced starch–lauric acid complex formation. Relative crystallinity of EN atoms treated lauric acid incorporated kithul starch samples increased with plasma power. Moreover, lower pasting property, storage modulus (G'), loss modulus (G''), hardness and higher Tanδ indicated decrease in gelation and retrogradation property. ENL-18 W showed the lowest complex viscosity (Ƞ*). Lauric acid incorporation in EN atoms treated kithul starch reduced in vitro digestibility and significantly (p ≤ 0.05) increased RS (resistant starch). Hence, EN atoms treatment on the kithul starch granules prior to fatty acid incorporation is an effective technique for the development of starch-fatty acid complexes.